Façade Compositions of the Early Renaissance Venetian Churches: Stating the Problem - Musina, Renata I. (Actual Problems of Theory and History of Art, 2021)
In the history of the early Italian Renaissance architecture in Venice, the issue of church facade design seems to be an exceptional phenomenon. Even before the strict classical compositions of Andrea Palladio and Sebastiano Serlio, Venetian architecture already had an elegant solution of the church facade based on the concept of the classical order — a trilobe scheme, reinterpreted in the façade of San Michele in Isola (1468–1479, Mauro Codussi). In the second half of the 15th century — the first third of the 16th century, this form determined the architectural agenda not only in Venice itself, but also in Dalmatia, its sphere of influence. At the same time, in Venice, there were several options for the composition of a church facade: semicircular lunettes and triangular pediments. In the context of the political and urban planning specifics of Venice, the design of a church facade was an independent task, and it had been successfully solved in the works of Mauro Codussi and Pietro Lombardo. Based on the analysis of the key monuments of the early Renaissance religious architecture of Venice, the article presents an attempt to highlight the main characteristics of the facade design issue and some further directions of the research.
Keywords: Venice; Mauro Codussi; Pietro Lombardo; Early Renaissance architecture; Dalmatia; façade composition; church architecture